Tracking morphological development in stony corals - Garrett J. Fundakowski; Viviana Brambilla; Kyle J. A. Zawada; Cher F. Y. Chow; Emily Croasdale; Amelia J. F. Errington; Luisa Fontoura; Wilhelm J. Marais; Rachael M. Woods; Pim Edelaar; Kevin Lala; Joshua S. Madin; et al. (Coral Reefs, 2026)

Investigating people’s perceptions of alien parakeets in urban environments - Joana Ribeiro; Inês Carneiro; Ana Nuno; Miguel Porto; Pim Edelaar; Álvaro Luna; Luís Reino (European Journal of Wildlife Research, 2021)

Lovebirds in the air: trade patterns, establishment success and niche shifts of Agapornis parrots within their non-native range - Emiliano Mori; Laura Cardador; Luís Reino; Rachel L. White; Dailos Hernández-Brito; Marine Le Louarn; Lorenzo Mentil; Pim Edelaar; Liviu G. Pârâu; Boris P. Nikolov; Mattia Menchetti (Biological Invasions, 2020)

Selection on a behaviour‐related gene during the first stages of the biological invasion pathway - Jakob C. Mueller; Pim Edelaar; Adrián Baños‐Villalba; Martina Carrete; Jaime Potti; Julio Blas; Jose Luis Tella; Bart Kempenaers (Molecular Ecology, 2017)
Human‐induced biological invasions are common worldwide and often have negative impacts on wildlife and human societies. Several studies have shown evidence for selection on invaders after introduction to the new range. However, selective processes already acting prior to introduction have been largely neglected. Here, we tested whether such early selection acts on known behaviour‐related gene variants in the yellow‐crowned bishop ( Euplectes afer ), a pet‐traded African songbird. We tested for nonrandom allele frequency changes after trapping, acclimation and survival in captivity. We also compared the native source population with two independent invasive populations. Allele frequencies of two SNP s in the dopamine receptor D4 ( DRD 4 ) gene—known to be linked to behavioural activity in response to novelty in this species—significantly changed over all early invasion stages. They also differed between the African native population and the two invading European populations. The two‐locus genotype associated with reduced activity declined consistently, but strongest at the trapping stage. Overall genetic diversity did not substantially decrease, and there is little evidence for new alleles in the introduced populations, indicating that selection at the DRD 4 gene predominantly worked on the standing genetic variation already present in the native population. Our study demonstrates selection on a behaviour‐related gene during the first stages of a biological invasion. Thus, pre‐establishment stages of a biological invasion do not only determine the number of propagules that are introduced (their quantity), but also their phenotypic and genetic characteristics (their quality).

Reproductive timing as a constraint on invasion success in the Ring-necked parakeet (Psittacula krameri) - Alvaro Luna; Detlev Franz; Diederik Strubbe; Assaf Shwartz; Michael P. Braun; Dailos Hernández-Brito; Yariv Malihi; Asaf Kaplan; Emiliano Mori; Mattia Menchetti; Chris A. M. van Turnhout; Dave Parrott; et al. (Biological Invasions, 2017)

The empty temporal niche: breeding phenology differs between coexisting native and invasive birds - Ana Sanz-Aguilar; Martina Carrete; Pim Edelaar; Jaime Potti; José L. Tella (Biological Invasions, 2015)

Shared genetic diversity across the global invasive range of the monk parakeet suggests a common restricted geographic origin and the possibility of convergent selection - Pim Edelaar; Severine Roques; Elizabeth A. Hobson; Anders Gonçalves da Silva; Michael L. Avery; Michael A. Russello; Juan C. Senar; Timothy F. Wright; Martina Carrete; José L. Tella (Molecular Ecology, 2015)
While genetic diversity is hypothesized to be an important factor explaining invasion success, there is no consensus yet on how variation in source populations or demographic processes affects invasiveness. We used mitochondrial DNA haplotypic and microsatellite genotypic data to investigate levels of genetic variation and reconstruct the history of replicate invasions on three continents in a globally invasive bird, the monk parakeet ( Myiopsitta monachus ). We evaluated whether genetic diversity at invasive sites could be explained by (i) the native source populations from which they were derived and (ii) demographic bottlenecks during introduction. Genetic data indicated a localized source area for most sampled invasive populations, with limited evidence for admixing of native source populations. This pattern largely coincides with historical data on pet trade exports. However, the invasive populations are genetically more similar than predicted from the export data alone. The extent of bottleneck effects varied among invasive populations. The observed low genetic diversity, evidence of demographic contraction and restricted source area do not support the hypothesis that invasion is favoured by the mixing and recombining of genetic variation from multiple source populations. Instead, they suggest that reduced genetic variation through random processes may not inhibit successful establishment and invasion in this species. However, convergent selection across invasive sites could also explain the observed patterns of reduction and similarity in genetic variation and/or the restricted source area. In general, the alternative explanation of intraspecific variation in invasive potential among genotypes or geographic areas is neglected, but warrants more attention as it could inform comparative studies and management of biological invaders.

If F ST does not measure neutral genetic differentiation, then comparing it with Q ST is misleading. Or is it? - PIM EDELAAR; MATS BJÖRKLUND (Molecular Ecology, 2011)
The comparison between neutral genetic differentiation ( F ST ) and quantitative genetic differentiation ( Q ST ) is commonly used to test for signatures of selection in population divergence. However, there is an ongoing discussion about what F ST actually measures, even resulting in some alternative metrics to express neutral genetic differentiation. If there is a problem with F ST , this could have repercussions for its comparison with Q ST as well. We show that as the mutation rate of the neutral marker increases, F ST decreases: a higher within‐population heterozygosity (He) yields a lower F ST value. However, the same is true for Q ST : a higher mutation rate for the underlying QTL also results in a lower Q ST estimate. The effect of mutation rate is equivalent in Q ST and F ST . Hence, the comparison between Q ST and F ST remains valid, if one uses neutral markers whose mutation rates are not too high compared to those of quantitative traits. Usage of highly variable neutral markers such as hypervariable microsatellites can lead to serious biases and the incorrect inference that divergent selection has acted on populations. Much of the discussion on F ST seems to stem from the misunderstanding that it measures the differentiation of populations, whereas it actually measures the fixation of alleles. In their capacity as measures of population differentiation, Hedrick’s G ′ ST and Jost’s D reach their maximum value of 1 when populations do not share alleles even when there remains variation within populations, which invalidates them for comparisons with Q ST .

Adaptive speciation theory: a conceptual review - Franz J. Weissing; Pim Edelaar; G. Sander van Doorn (Behavioral Ecology and Sociobiology, 2011)